Purine-rich enhancers function in the AT-AC pre-mRNA splicing pathway and do so independently of intact U1 snRNP. - Wu, Q (1998)
A rare class of introns in higher eukaryotes is processed by the recently discovered AT-AC spliceosome. AT-AC introns are processed inefficiently in vitro, but the reaction is stimulated by exon-definition interactions involving binding of U1 snRNP to the 5' splice site of the downstream conventional intron. We report that purine-rich exonic splicing enhancers also strongly stimulate sodium channel AT-AC splicing. Intact U2, U4, or U6 snRNAs are not required for enhancer function or for exon definition. Enhancer function is independent of U1 snRNP, showing that splicing stimulation by a downstream 5' splice site and by an exonic enhancer differ mechanistically.